Secukinumab demonstrates high efficacy and a favourable safety profile in paediatric patients with severe chronic plaque psoriasis: 52‐week results from a Phase 3 double‐blind randomized, controlled trial. (19th January 2021) - Bodemer, C.; Kaszuba, A.; Kingo, K.; Tsianakas, A.; Morita, A.; Rivas, E.; Papanastasiou, P.; Keefe, D.; Patekar, M.; Charef, P.; Zhang, L.; Cafoncelli, S.; et al.
Abstract: Background: Secukinumab has demonstrated sustained long‐term efficacy with a favourable safety profile in various psoriatic disease manifestations in adults. Objectives: Here, the efficacy and safety of two secukinumab dosing regimens [low dose (LD) and high dose (HD)] in paediatric patients with severe chronic plaque psoriasis over one year are reported. Methods: In this multicentre, double‐blind study (NCT02471144), patients aged 6 to <18 years with severe chronic plaque psoriasis were stratified and randomized by weight (<25 kg, 25 to <50 kg, ≥50 kg) and age (6 to <12 years, 12 to <18 years) to receive low‐dose (LD: 75/75/150 mg) or high‐dose (HD: 75/150/300 mg) subcutaneous secukinumab or placebo or etanercept 0.8 mg/kg (up to a max of 50 mg). Results: Overall, 162 patients were randomized to receive secukinumab LD ( n  = 40) or HD ( n  = 40), etanercept ( n  = 41) or placebo ( n  = 41). The co‐primary objectives of the study were met with both secukinumab doses (LD and HD) showing superior efficacy compared to placebo ( P  < 0.0001) with respect to PASI 75 response (80.0%, 77.5% vs. 14.6%) and IGA mod 2011, 0 or 1 response (70%, 60% vs. 4.9%) at Week 12. Both secukinumab doses were superior to placebo ( P  < 0.0001) with respect to PASI 90 response at Week 12 (72.5%, 67.5% vs. 2.4%). The efficacy of both doses was sustained to Week 52 with secukinumab achieving higher responses vs. etanercept (PASI 75/90/100: LD, 87.5%/75.0%/40.0% and HD, 87.5%/80.0%/47.5.% vs. etanercept, 68.3%/51.2%/22.0% and IGA 0 or 1: LD, 72.5% and HD, 75.0% vs. etanercept, 56.1%). The safety profile of secukinumab was consistent with the adult Phase 3 studies, with no new safety signals identified. Conclusions: Both doses of secukinumab demonstrated high and sustained efficacy up to Week 52 with a favourable safety profile in paediatric patients with severe chronic plaque psoriasis.